Simulation of water and nitrogen dynamics in a Cerrado soil under coffee cultivation using SWAP and ANIMO models - Pinto, Victor Meriguetti (2016)
Agriculture when only focused on production leads to an unsustainable use of inputs with negative consequences to the environment and human health. One consequence of the excessive use of fertilizers is the pollution of surface and underground water resources in agricultural eco-systems and their boundaries. The Brazilian Cerrado has been suffering the transformations of the intensive agriculture during the last decades. Due to the poor fertility of soils, in general very sandy and of low pH, the use of agricultural inputs is intensified and the nutrient downward transport by leaching becomes a serious problem in different regions. Information about the current use practices of fertilizer use in the Cerrado environment must be gathered for a healthy transition of this biome. Models based on physical and chemical processes are useful tools to simulate water and nutrient dynamics in agricultural systems, including the related losses due to adopted managements. They have the potential to evaluate different scenarios to predict outcomings of such practices. Among the available models for such processes, SWAP (Soil, Water, Atmosphere and Plant model) has been used under several agronomic conditions to describe hydrologic processes, and ANIMO (Nitrogen in Agriculture model) to simulate N cycling in agricultural systems. Our study presents an application of SWAP to adult perennial coffee crops along one productive cycle, with focus on deep drainage losses and irrigation management in a representative Brazilian Cerrado management system. The SWAP/ANIMO combination was used in this study to simulate N absorption by coffee plants and N leaching in the form NO3-N, as a result of an intensive fertilizer management practice. The ANIMO program was calibrated in relation to one N treatment, of 400 kg ha-1 year-1, and was evaluated with independent data of NO3-N in soil solution of another treatment of 800 kg ha-1 year-1. The yearly water balance (WB) obtained from SWAP was similar to that obtained through a sequential climatologic WB of Thornthwaite and Matter. However, the monthly deep drainage values obtained by SWAP as compared to the WB values presented differences with a determination coefficient of 0.77 in a linearization of the results. Irrigation scenarios with intervals of 3(IF3), 5(IF5), 10 (IF10) e 15 (IF15) days between water applications were simulated by SWAP and compared with the irrigation management practiced in the farm where the experiment was carried out. These simulations showed for longer intervals (IF15) drainage losses were smaller, water productivity higher, as well as relative productivity. Measurements of N absorption by plants obtained experimentally were similar to ANIMO simulations. Sensitivity analyses of the model showed that leaching and soil solution concentration of NO3-N are sensitive to soil pH and temperature of the decomposition processes. We conclude that the combination of SWAP with ANIMO was efficient for the description of the N cycle in a Cerrado soil-plant-atmosphere system